Embracing the Internet of Things for Language Education: Are We There Yet? - Hafizoah, Kassim; Asiah, Kassim (UMP Press, 2019)
The fourth industrial revolution (41R) has just begun, and already its impact on every part of our lives is massive. The fundamental change of this revolution is clearly defined by the burgeoning transformation of the so-called 'technology' and all things related including the humankind (Schwab, 2016). The term is coined by Klaus Schwab, the Founder and Executive Chairman of the World Economic F arum (WEF) in 2017, proclaiming that it is building on the third industrial revolution. Historically, this impactful revolution, from its first stage in the late 1800s, is founded on technology. This transformation begun when people realized what technology is capable of, and ultimately in order to mass produce systematically and efficiently to fulfill the needs of the ever increasing human population (Effoduh, 2016; Penphrase, 2018).